<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1997 - OZEKI, Jun; KUNITAKE, Manabu; IGARASHI, Kiyoshi (National Institute of Polar Research, 1999)
P(論文) departmental bulletin paper